Pengaruh Pemberian Edukasi Melalui Whatsapp Dan Zoom Terhadap Pengetahuan Dan Praktik Pengendalian Hipertensi Pada Pasien Hipertensi Di Puskesmas Rejosari Tahun 2021 - Igha Viorela Br Karo Sekali; Reno Renaldi; Yuyun Priwahyuni; Mitra Mitra; Emy Leonita (Jurnal Kesehatan Komunitas, 2022)
Based on the results of interviews with hypertensive patients at the Rejosari Health Center, Pekanbaru City, it was found that the patient's knowledge about hypertension and patient behavior in hypertension control practices was still low. So it is necessary to do education via whatsapp and zoom during this covid 19 period. This study was to determine the effect of providing education through WhatsApp and Zoom on knowledge and practice of controlling hypertension in patients. This type of research is analytic with quantitative methods with a Quasy Experiment design in the form of a Pretest-Postest With Control Group design. The research sample amounted to 32 people in the control group and 32 people in the experimental group. The population in this study was 418. The sampling technique used consecutive sampling, to obtain data in the study, it was done by filling out a google form. The data analysis used was Univariate, Bivariate, and Multivariate. Research results in There is an effect of providing education to the whatsapp group and zoom group on the knowledge and practice of controlling hypertension patients. However, WhatsApp education is more dominant in influencing knowledge and practice of controlling hypertension in hypertensive patients at the Rejosari Health Center Pekanbaru City in 2021 after being controlled by the variables of gender, occupation, education, and age.